2019
DOI: 10.1177/2333721419843707
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Marijuana Use and Health Impact: A Survey Among Older Coloradans

Abstract: Access to recreational and medical marijuana is common in the United States, particularly in states with legalized use. Here, we describe patterns of recreational and medical marijuana use and self-reported health among older persons using a geographically sampled survey in Colorado. The in-person or online survey was offered to community-dwelling older persons aged above 60 years. We assessed past-year marijuana use including recreational, medical, or both; methods of use; marijuana source; reasons for use; s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 23 publications
(27 reference statements)
7
29
0
Order By: Relevance
“…Second, despite increased likelihoods of social and structural vulnerabilities (e.g., homelessness, incarceration) in the recreational use class, several positive health outcomes (e.g., better self-perceived general health, less pain, less anxiety, lack of diagnosed mental illness, HIV-negative) were associated with membership in the class, while members of the classes characterized by therapeutic use tended to exhibit poorer indicators of health. These patterns are likely indicative of frequent cannabis use to address poor health rather than poor health resulting from frequent cannabis use, as has been described previously [34,35]. Our findings suggest that daily cannabis use among PWUD may signify an unmet healthcare need, such as underor unmanaged chronic pain or mental illness.…”
Section: Plos Onesupporting
confidence: 73%
“…Second, despite increased likelihoods of social and structural vulnerabilities (e.g., homelessness, incarceration) in the recreational use class, several positive health outcomes (e.g., better self-perceived general health, less pain, less anxiety, lack of diagnosed mental illness, HIV-negative) were associated with membership in the class, while members of the classes characterized by therapeutic use tended to exhibit poorer indicators of health. These patterns are likely indicative of frequent cannabis use to address poor health rather than poor health resulting from frequent cannabis use, as has been described previously [34,35]. Our findings suggest that daily cannabis use among PWUD may signify an unmet healthcare need, such as underor unmanaged chronic pain or mental illness.…”
Section: Plos Onesupporting
confidence: 73%
“…Reynolds et al completed a survey among 345 patients in a geriatrics clinic at the University of Colorado in 2016 to 2017 and found 32% of patients used cannabis at least once in their lifetimes, and the common reasons for cannabis use were for pain and sleep disorders 21 . Lum et al conducted a survey among community‐dwelling adults aged 60 years and older in Colorado, and found that older adults were likely to report using cannabis for both recreational and medical purposes and generally thought cannabis had a positive impact on their lives 22 . Brown et al studied data in the Florida Medical Marijuana Use Registry and found that over half of those registered were older adults, and the most common reason for cannabis use was for chronic pain 23 .…”
Section: Introductionmentioning
confidence: 99%
“…One might thus argue for the existence of a "gender effect". With cannabis consumption being more popular among men than women [104] and considering that individuals who already have consumed cannabis seem to be more disposed to use it as a therapeutic agent, it is possible that men are more prone to using cannabis for therapeutic purpose than women [34].…”
Section: Strengths and Limitations Of The Reviewmentioning
confidence: 99%